Effect of Egg Replacers in Soft Drop Cookies - Brackebusch, Katherine H. (My University, 2017)
The purpose of this research was to find an optimal method of replacing eggs in soft drop cookies. This avenue of research is valuable because many large-scale bakeries can improve their production process through the elimination of this ingredient. Eggs are part of a volatile agricultural market, making their availability and price vary greatly. They also contribute a food safety concern and a common allergen. By eliminating eggs from their formulas, industry professionals can not only improve the price stability of their process, but also increase the safety of their product and reach a larger consumer base that now includes individuals avoiding eggs. This research evaluates the effectiveness of several commercial egg replacers as well as the benefit of adding additional functional ingredients, a dough conditioner and an emulsifier, to commercial egg replacers.